Alfalfa (Medicago sativa L.) overseeding on mature switchgrass (Panicum virgatum L.) stand: biomass yield and nutritive value after the establishment year - Mantino, Alberto; Ragaglini, Giorgio; Nassi o di Nasso, Nicoletta; Tozzini, Cristiano; Taccini, Fabio; Bonari, Enrico (Italian Journal of Agronomy, 2016)
Perennial crops can positively act on the environment providing a better inter-annual protection of soil cover from water erosion, limiting soil fertility degradation, the risk of nutrient leaching and the exploitation of water for irrigation. Switchgrass (Panicum virgatum L.), a warm-season grass native from North America, has been cultivated for decades as forage crop and only recently as bioenergy crop. Even if several studies reported a positive effect of nitrogen (N) supply on switchgrass yield and quality, potential indirect and direct environmental risks (e.g., eutrophication and greenhouse gas emission) are related to this practice. For this reason grass-legume intercropping can represent a sustainable practice able to increase biomass yield and quality, and at the same time to improve N use efficiency, soil structure and fertility. Based on this, the aim of this study was to evaluate the suitability of switchgrass to Mediterranean environment as forage crop and to improve biomass yield and its nutritional value by intercropping with alfalfa (Medicago sativa L). During spring 2013, in two switchgrass pure stands (varieties Alamo and Blackwell, respectively), alfalfa was established through direct seeding implementing a split-plot experimental design. Our first year results report a positive effect of the intercropping in increasing the total annual yield of the stand, of about 20% with respect to the pure switchgrass stand. However, the presence of alfalfa negatively affected switchgrass yield in the mixture. In both varieties, the crude protein content was higher in the mixture than in the pure switchgrass stands. Conversely, the neutral detergent fibre content in the mixture was lower than in pure switchgrass. Then, our results show that switchgrass-alfalfa intercropping leads to increase the profitability of grassland-based livestock production.